Effect of Supplementation of soybean Cake and Fishmeal with Lysine and Methionine in Broiler Diets on the Growth Performance of Turkey Poults (Nepal Agriculture Research Journal, 2009)
The study was carried out during June to August 2003, using one hundred and eight day oldturkey poults which were randomly divided into twelve groups, 9 birds in each. Three replicatewere allocated to each four dietary treatments. Commercially available broiler feed (Ratna feed)was considered as basal diet (Diet-1), Diet-2 was prepared by addition of lysine (0.3%) +methionine (0.1%) to Diet-1, Diet-3 was prepared by supplementation of soybean cake (15%) +lysine (0.2%) + methionine (0.1%) to Diet-1and Diet-4 was formulated by addition of soybeancake (10%) + fishmeal (5%) in Diet-1. Each diet was offered ad lib. from one week to 10 weeksof age. Observation on weekly body weight, weekly and cumulative feed consumed wasaccessed. Weekly body weight gain and feed conversion ratio was calculated. Economics ofdietary treatments in terms of income over chicks and feed cost was also calculated.Significantly higher body weight (P < 0.01) was observed in birds fed with Diet-3 (1881.5 ± 17g), followed by Diet-4 (1745.3 ± 33 g) and Diet-2 (1460.8 ± 51 g) as compared to Diet-1 (1125.2± 20 g) up to 10 weeks of age. The birds fed with supplemented diet consumed significantly (P